Prinsip Kesantunan Berbahasa Dosen dan Mahasiswa di Kelas Pembelajaran Bahasa Inggris sebagai Bahasa Asing (EFL) - Vidya Arisandi; Ajat Sudrajat; Yeni Fajrin; Fidela Cahya Camilla; Muhammad Fadly Saputra Pratama (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
This investigation examines the implementation of linguistic politeness in English as Foreign Language (EFL) instruction in Karawang, with particular emphasis on faculty-student interactions. Utilizing an ethnographic qualitative methodology, the research encompasses one faculty member and thirty-five, first-semester students. Data acquisition was conducted through non-participant classroom observations and semi-structured in-depth interviews. The findings demonstrate that the faculty member systematically implemented politeness strategies through indirect communication and face-threatening acts management. The incorporation of Sundanese cultural values in instruction was manifested in the utilization of address systems and modifications in communication approaches. The implementation of politeness significantly contributed to the enhancement of students' communicative competence and the establishment of a conducive learning environment. This research underscores the significance of integrating linguistic politeness and indigenous cultural values in EFL instruction to facilitate pedagogical effectiveness.